A Systematic Review of the Trends Research Creative Thinking Skills in Students' Physics Learning (2015-2024) - Aris Doyan; Susilawati Susilawati; Syarful Annam; Lalu Muliyadi; Ruth Rize Paas Megahati; Risnawati Agustin Hutabarat; Muhammad Ikhsan; Nuraini Rachma Ardianti; Hamidi Hamidi (Jurnal Penelitian Pendidikan IPA, 2024)
Creative thinking skills are ability found many possible answers to a problem, where the emphasis is on quantity, appropriateness, and diversity of answers. Where the answer in question is an answer that correct and varied. This research aims to identify and analyze research trends in the creative thinking ability in physics learning. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research on creative thinking ability in physics learning that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend on the creative thinking skills in physics learning indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. However, in 2023 there will be a decline in the research trend on the creative thinking skills in physics learning. There are many documents in the form of articles, proceedings, chapters, preprints, edited books and monograph that discuss research into the creative thinking skills in physics learning. Key words that are often used in research on the creative thinking skills in physics learning are critical thinking, STEM, PjBL, PBL, technology, virtual laboratory, etc.